Effectiveness of levamisole in the treatment of patients with severe COVID-19: a randomized controlled clinical trial - Pourahmad, Morteza; Soltani, Rasool; Noroozi, Mohammad H; Khorvash, Farzin; Ataei, Behrooz; Shams, Manijeh; Nikokar, Fatemeh (The Journal of Infection in Developing Countries, 2024)
Introduction: Inflammation plays a role in coronavirus disease 2019 (COVID-19) pathophysiology and anti-inflammatory drugs may help reduce the disease severity. Levamisole is an anthelmintic drug with immunomodulatory and possible antiviral effects. This study aimed to evaluate the role of levamisole in the treatment of patients with COVID-19. Methodology: In this randomized controlled clinical trial, hospitalized patients with confirmed severe COVID-19 (arterial oxygen saturation < 90%) were randomly assigned to either experimental (n = 41) or control (n = 45) groups. Levamisole 50 mg orally daily was prescribed for the first group until discharge or death, for a maximum of 7 days, along with other standard treatments. Only standard treatments were prescribed to the control group. Clinical response (either improvement or failure) at the end of the fifth and seventh days, changes in laboratory indices, length of hospitalization, and mortality rate during the study were evaluated and recorded. Results: The rate of clinical improvement in the experimental group was significantly more than in the control group on the fifth (97.6% vs. 58.7%, p < 0.001) and seventh (95.8% vs. 66.7%, p = 0.007) days. Furthermore, the mean length of hospital stays in the experimental group (8.39 ± 3.54 days) was significantly shorter than in the control group (10.78 ± 5.40 days, p = 0.024). No patients died during the study. Conclusions: Administering levamisole to hospitalized patients with severe COVID-19 reduced hospitalization time and improved several clinical outcomes.